Research on Cab Vibration Control Based on Parameter Hierarchical Interaction Model - Enyong Xu; Shuilong He; Weiguang Zheng; Tao Tang; Chao Li; Qibai Huang (Shock and Vibration)
The vibration level of a cab affects the passenger’s ride comfort and safety significantly. It is of great importance to control the vibration level of cabs under various driving conditions. The associated vibration transfer paths of cabs are studied by using a hierarchical analysis method of a parameter index. The multiobjective design analysis is carried out by using the multiparameter joint optimisation design. Further, the optimal control of the cab vibration level is obtained from a full-condition simulation environment. Additionally, a multibody vehicle model is established. The simulation analysis under multiple working conditions is conducted. The optimal parameter distribution of the cab mounting structure was established by analysing the influence of the design parameters and experimental verification. This greatly improves the comfort of the cab.